Comparison of the effectiveness of four organic chemoattractants towards zoospores of Ulva pertusa and macrofouling - Lee, Ji Hyun; Sidharthan, Mohandoss; Jung, Sang Mok; Jo, Qtae; Rahman, Mohammad Mustafizur; Shin, Hyun Woung (Triveni Enterprises, Lucknow (India), 2008)
Algal spores respond to many environmental variables, especially, to chemical “cues”. This chemotactic response can be utilized to attract spores, thereby colonization of a new substrata is possible to be influenced. In this attempt, four chemoattractant candidates were screened against spores of Ulva pertusa to reveal their efficiencies. Attachment and subsequent germination of Ulva spores were effectively influenced by these chemoattractant candidates. In particular, 100 &g cm-2 of D-glucose coating was found to enhance spore attachment by >150%. Furthermore, field investigations carried out with test panels, clearly indicate the chemoattractive properties of test coatings. In recent years, various anthropogenic activities and natural hazards cause detrimental impacts on the benthic algae and other fishery resources. Artificial reefs have been laid on many coastal regions to increase or restore marine resources. Chemoattractant coatings can be applied on artificial surfaces to increase the colonization of benthic forms. It also can be used in the mariculture devices. Influence of chemoattractants on Ulva spores and fouling biomass estimated on test panels are discussed.